2013
DOI: 10.1093/hmg/ddt614
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced epigenetic modifications are associated with cardiac tissue fibrosis and the development of a myofibroblast-like phenotype

Abstract: Ischemia caused by coronary artery disease and myocardial infarction leads to aberrant ventricular remodeling and cardiac fibrosis. This occurs partly through accumulation of gene expression changes in resident fibroblasts, resulting in an overactive fibrotic phenotype. Long-term adaptation to a hypoxic insult is likely to require significant modification of chromatin structure in order to maintain the fibrotic phenotype. Epigenetic changes may play an important role in modulating hypoxia-induced fibrosis with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
205
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(224 citation statements)
references
References 27 publications
8
205
0
Order By: Relevance
“…An upregulation and increased secretion of miR-29a, as a secondary effect of Dnmt3a inhibition in modified CPCs, may participate to the beneficial antifibrotic effect we observed in vivo. Moreover, in human cardiac tissue, profibrotic changes induced by prolonged hypoxia during MI are associated with a global DNA hypermethylation and increased expression of Dnmt1 and Dnmt3b enzymes (42). Indeed, Dnmt3-induced hypermethylation of antifibrotic genes, such as THY-1 (43) or RASSF1A (44), was shown to contribute to fibroblast activation and fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…An upregulation and increased secretion of miR-29a, as a secondary effect of Dnmt3a inhibition in modified CPCs, may participate to the beneficial antifibrotic effect we observed in vivo. Moreover, in human cardiac tissue, profibrotic changes induced by prolonged hypoxia during MI are associated with a global DNA hypermethylation and increased expression of Dnmt1 and Dnmt3b enzymes (42). Indeed, Dnmt3-induced hypermethylation of antifibrotic genes, such as THY-1 (43) or RASSF1A (44), was shown to contribute to fibroblast activation and fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, TGF-β can induce both hypermethylation and hypomethylation, illustrating the complexities of the pathways that control and alter methylation patterns. Interestingly, treatment with 5-aza-2'-deoxycytidine abrogates the effects of TGF-β induced myofibroblasts in cardiac cells (Watson et al, 2014).…”
Section: Tgf-βmentioning
confidence: 97%
“…It has found a sufficient difference in DNA methylation in promoters of up-regulated genes, but not down-regulated genes in end-stage cardiomyopathy [40]. Furthermore, the process of DNA methylation was under regulation through several genetic pathways that are modulating by platelet/ endothelial cell adhesion molecule 1, hypoxia-inducible factor1alpha, angiomotin-like 2, and Rho GTPase activating protein 24 [40,41] . Authors suggested that epigenetic modifications identified in failing heart might affect cardiac function directly through regulation of structure protein synthesis and, however, indirectly via increased activity of cardiac fibroblasts due to prolonged hypoxia contributing to the pro-fibrotic nature of the ischemic milieu.…”
Section: Histone Acetylationmentioning
confidence: 99%